Die ontwikkeling vanaf "n simplistiese na "n gevorderde agrariese ekonomie in die leefwêreld van die Bybel - Volschenk, G. J. (HTS teologiese studies, 2002)
The development of the agrarian society of the Bible from a simplistic to an advanced agrarian societyThe aim of this article is to study the development of the ancient economy from a simplistic agrarian society to an advanced agrarian society. The Hasmonian Empire formed the bridge from a simplistic to an advanced agrarian society. The Roman Empire was the end product of the evolution process and an example of the advanced agrarian society.